2015
DOI: 10.1007/s10616-014-9800-6
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of a monoclonal antibody against the putative T cells of Labeo rohita

Abstract: In this study, we have described the development and characterization of monoclonal antibodies (MAbs) directed against thymocytes of rohu, Labeo rohita. MAbs were obtained by immunizing BALB/c mice with freshly isolated and nylon wool column enriched mononuclear cells of thymus. Positive clones against thymocytes were screened by cellular ELISA. The hybridoma showing strong reactivity with nylon wool enriched mononuclear cells, and non-reactivity with a rohu thymus macrophage cell line and rohu serum was selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Accordingly, it was suggested that the presence of CD4-positive T cells in the ginbuna crucian carp is the equivalent of the helper T-lymphocyte in mammals. Additionally, mAbs directed against thymocytes of rohu, ( Labeo rohita ) was developed and characterized [32]. This mAbs emerged to be a suitable marker for T-lymphocytes and could be a valuable tool in studying the immune response and ontogeny of the rohu immune system.…”
Section: Antibodies Used To Study the Expression Of Cd4+ T Cells In Fishmentioning
confidence: 99%
“…Accordingly, it was suggested that the presence of CD4-positive T cells in the ginbuna crucian carp is the equivalent of the helper T-lymphocyte in mammals. Additionally, mAbs directed against thymocytes of rohu, ( Labeo rohita ) was developed and characterized [32]. This mAbs emerged to be a suitable marker for T-lymphocytes and could be a valuable tool in studying the immune response and ontogeny of the rohu immune system.…”
Section: Antibodies Used To Study the Expression Of Cd4+ T Cells In Fishmentioning
confidence: 99%
“…In addition, cd4-1 , the gene encoding the T cell co-receptor, was also upregulated in infected salmon ( 34 ), all indicating that PRV elicited the adaptive immune response in Atlantic salmon, which probably involves T cell proliferation. CD4 + CD3 + T cells (T helper) have been in fact identified, isolated and characterized in some fish species, including Japanese Pufferfish ( Takifugu rubripes ), ginbuna crucian carp ( Carassius auratus langsdorfii ), zebrafish ( Danio rerio ), rainbow trout ( Oncorhynchus mykiss ) ( 42 47 ); and rohu ( Labeo rohita ) ( 48 ). Although in Atlantic salmon, T cell isolation and characterization awaits further studies, transcriptional data and the studies in rainbow trout ( 44 , 49 52 ) support the presence of T lymphocytes in this fish species and its role in response to the pathogens or model antigens.…”
Section: Immune Response Against Prv Infectionmentioning
confidence: 99%
“…To date, MAbs have been established for a variety of freshwater and marine fish species. These include Ictalurus punctatus (Edholm et al, 2010), Paralichthys olivaceus (Li et al, 2007), Takifugu rubripes (Miyadai et al, 2004), Labeo rohita (Rathore et al, 2008), Channa striata (Sood et al, 2011), Clupea pallasii (Purcell et al, 2012), Clarias batrachus (Sood et al, 2012), Labeo rohita (Rebello et al, 2016), Lateolabrax japonicas (Yang et al, 2018), Oncorhynchus mykiss (Hayashi et al, 2019) and Carassius auratus gibelio (Wu et al, 2020). All of these MAbs developed have numerous diagnostic applications in fish health management.…”
Section: Introductionmentioning
confidence: 99%